Feminists against Fascism: India’s Female Muslim Protest - Mr. Abu al-Hassan; Dr. Ghazali Tufail (Al-Qanṭara, 2023)
This article examines debates about India, citizenship, and nationhood through the eyes of Indian Muslim female university students in Delhi. The Hindu majority administration adopted new citizenship legislation in December 2019. It sparked significant outrage because of its negative ramifications for Muslims and a big segment of the socioeconomically disadvantaged population. As a result, millions of people, mostly Dalits, Adivasis, and Bahujans, took to the streets to protest. Young Muslim female students and women rose to the forefront of a serious public debate for the first time. This scenario shattered the popular idea of repressed Muslim women who lack public voice and agency. This article draws on the accounts of Indian Muslim female students who took part in these protests to show their perceptions of, and discussions with, the authorities. Keyword- Indian Muslim, Feminists against Fascism, and Muslim Protest